2016
DOI: 10.1161/atvbaha.115.306578
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction in Human Diabetes Is Mediated by Wnt5a–JNK Signaling

Abstract: Objectives Endothelial dysfunction is linked to insulin resistance, inflammatory activation and increased cardiovascular risk in diabetes mellitus; however the mechanisms remain incompletely understood. Recent studies have identified pro-inflammatory signaling of Wnt5a through JNK as a regulator of metabolic dysfunction with potential relevance to vascular function. We sought to gain evidence that increased activation of Wnt5a-JNK signaling contributes to impaired endothelial function in patients with diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 52 publications
7
85
1
Order By: Relevance
“…During ER stress, IRE1α and PERK‐ATF4 trigger the activation of JNK, a key inflammatory signaling pathway 43, 44, 45. Interestingly, we have previously reported an enhanced activation of JNK in patients with DM, that contributes to reduced nitric oxide production and lower flow‐mediated dilatation 30. In the present study, we develop evidence that ER stress pathways may be an important regulator of JNK activation in the vasculature in patients with DM by demonstrating increased activation of both the IRE1α and PERK pathways.…”
Section: Discussionmentioning
confidence: 98%
“…During ER stress, IRE1α and PERK‐ATF4 trigger the activation of JNK, a key inflammatory signaling pathway 43, 44, 45. Interestingly, we have previously reported an enhanced activation of JNK in patients with DM, that contributes to reduced nitric oxide production and lower flow‐mediated dilatation 30. In the present study, we develop evidence that ER stress pathways may be an important regulator of JNK activation in the vasculature in patients with DM by demonstrating increased activation of both the IRE1α and PERK pathways.…”
Section: Discussionmentioning
confidence: 98%
“…Their findings indicate potential burden of commercial sugar-sweetened beverage consumption on public health in general and the downside of hyperglycemia in patients with diabetes mellitus that are closely related with cardiovascular disease in particular. Bretón-Romero et al 61 showed that wingless-type family member 5a/c-jun N terminal kinase pathway contributed to endothelial dysfunction associated with diabetic patients. Walther et al 62 demonstrated that not only endothelium-dependent but also endotheliumindependent vasodilatations in both micro-and macrocirculation were impaired in association with systemic inflammation in patients with metabolic syndrome with diabetes mellitus.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…15,80 However, many molecular mechanisms have been identified which with aging or under pathological conditions (obesity, diabetes mellitus, and systemic or pulmonary hypertension) impair the production of NO by eNOS and precipitate endothelial dysfunction. Major causes include increased production of ROS (causing S-glutathionylation of eNOS and uncoupling/inactivating the enzyme), 123,124 augmented presence of oxidized-LDL (causing reduced turnover, uncoupling, and dephosphorylation of eNOS) or carbamylated-LDL, 125 activation of toll-like receptors (TLR; key components of innate immunity responses) of type 4 (TLR4; stimulated by circulating lipopolysaccharides) and the downstream NFκB pathway, 126 insulin resistance (favoring proinflammatory signaling of wingless-type family member 5a activating c-Jun NH 2 -terminal mitogenactivated PK), 127 increased expression of peptidyl prolyl cis-trans isomerase (in diabetic patients; causing isomerization of the inhibitory Ser116 of eNOS), or increased levels of plasma fatty acids (during hypertension and in obesity; promoting repalmitoylation for caveolae docking [see PostTranslational Modulation of eNOS Activity section of this article], thus favoring the inhibitory interaction of eNOS with caveolin-1). 15,98,117 Other chronic deleterious influences ).…”
Section: Reduced Protein Dimerizationmentioning
confidence: 99%